Internalizing Dzikir Values in Developing Students’ Spiritual Intelligence: A Multi-Site Study at Nurul Abror and Nurul Jadid Islamic Boarding School - Suyono; Mundir; A. Suhardi (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This research aims to investigate how the value of dhikr is internalized in the creation of the spiritual intelligence of students at two Islamic boarding schools with distinct methods and features. The main objective of this study is to understand how the methodical and contemplative practice of dhikr can influence a santri's spiritual outlook, religious respect, and spiritual consciousness. Utilizing qualitative approaches and a case-study design spanning multiple sites, this study is conducted at Pondok Pesantren Nurul Abror AlRobbaniyin in Banyuwangi and Pondok Pesantren Nurul Jadid in Bali. The research findings demonstrate that the value of dhikr is internalized through examples, routines, and the development of spiritual meaning, all of which contribute to the overall character of a santri. The presence of serenity, a sense of purpose in life, and solid religious and social ideals — all of which are signs of spiritual intelligence — is favorably affected by dhikr. This study contributes to the literature on Islamic education by presenting a thorough model of dhikr development, and it makes a theoretical contribution by integrating the concepts of tazkiyatun nafs, affection value, and spiritual quotients.